Romania Early Childhood Development : SABER Country Report 2019 - Adams, Lindsay (World Bank, Washington, DC, 2020)
Romania has clear separate legal frameworks for the health sector, requiring provision of services for pregnant women and young children; for the social and child protection and education sectors, including a mandatory pre-primary year of attendance. In recent years, early childhood development (ECD) has received broader attention from the Romanian Government as the early ages become a priority at the European Union and global levels. Systems approach for better education results (SABER) - ECD collects, analyzes, and disseminates comprehensive information on ECD policies around the world. The SABER-ECD framework presents a holistic and integrated assessment of how the overall policy environment in a country affects young children’s development. This assessment can be used to identify how countries address the same policy challenges related to ECD, with the ultimate goal of designing effective policies for young children and their families. SABER-ECD identifies three core policy goals that countries should address to ensure optimal ECD outcomes: establishing an enabling environment, implementing widely and monitoring, and assuring quality.